Global Trends in Blue Carbon Research in Mangroves (Agro Productividad, 2024)
Objective: To identify the central themes and research trends on blue carbon in mangroves through a bibliometric analysis of the existing global scientific literature.Design/Methodology/Approach: A total of 1,128 scientific documents from the period 1986-2023 were analyzed, obtained from the Scopus database. The Bibliometrix package in R Studio and VOSviewer were used for processing.Results: The results, encompassing 4,602 authors, 94 countries, 64 research areas, and 346 journals, indicated an exponential growth (R² = 0.99) in mangrove carbon research. The most productive author, country, research area, and journal were Lovelock, L. C., the United States of America, environmental sciences, and Science of The Total Environment, respectively. The studies focused on four thematic clusters: carbon storage, sedimentation, carbon dynamics, and climate change and anthropogenic impact. Topics related to blue carbon, carbon stores, climate change, restoration, and remote sensing are currently of significant interest to the scientific community.Study Limitations/Implications: While Scopus covers a vast number of peer-reviewed journals, it may omit some relevant research on the topic. Although the main research themes were identified, more in-depth information on each of them is still needed.Findings/Conclusions: Four globally relevant themes in blue carbon research in mangroves were identified, providing a roadmap for researchers to strategically direct efforts and funding in future scientific investigations.